Drosophila genetics - the first 25 years - Lindsley, Dan (Henry Stewart Talks, 2008)
Sex linked inheritance, linkage and linear chromosome maps, Non-disjunction, Genic balance theory of sex determination, Chromosome aberrations, Mutational studies of the gene, X-ray induction of gene and chromosome mutations, Cytological dissection of the X chromosome, Mitotic cytology, Polytene cytology
Reviewed at 2018/05/31